John Hancock papers - Hancock, John, 1737-1793.
Transcripts, made by Hancock and his secretary, of letters (1775-1776) from George Washington, Philip Schuyler, and Benedict Arnold; transcripts made by Peter Force of letters (1775-1777) written by Hancock while President of the Continental Congress; Hancock's original account with the U.S.; transcripts of a rough journal (1774 September-October) of the Continental Congress; and miscellaneous letters.
In part, transcripts and photocopies.
National Archives and Records Service (Record Group 360: Papers of the Continental Congress).
Politician, governor, and U.S. delegate to the Continental Congress from Massachusetts.
Collection material in English.
Keywords: Arnold, Benedict, -- 1741-1801.; Force, Peter, -- 1790-1868.; Schuyler, Philip John, -- 1733-1804.; Washington, George, -- 1732-1799.; United States. -- Continental Congress; Delegates, U.S. Continental Congress -- Massachusetts; Governors -- Massachusetts; Politicians